Dosimetric comparison between volumetric modulated arc therapy planning techniques for prostate cancer in the presence of intrafractional organ deformation. (21st December 2020) - Varnava, Maria; Sumida, Iori; Oda, Michio; Kurosu, Keita; Isohashi, Fumiaki; Seo, Yuji; Otani, Keisuke; Ogawa, Kazuhiko
Abstract: The purpose of this study was to compare single-arc (SA) and double-arc (DA) treatment plans, which are planning techniques often used in prostate cancer volumetric modulated arc therapy (VMAT), in the presence of intrafractional deformation (ID) to determine which technique is superior in terms of target dose coverage and sparing of the organs at risk (OARs). SA and DA plans were created for 27 patients with localized prostate cancer. ID was introduced to the clinical target volume (CTV), rectum and bladder to obtain blurred dose distributions using an in-house software. ID was based on the motion probability function of each structure voxel and the intrafractional motion of the respective organs. From the resultant blurred dose distributions of SA and DA plans, various parameters, including the tumor control probability, normal tissue complication probability, homogeneity index, conformity index, modulation complexity score for VMAT, dose–volume indices and monitor units (MUs), were evaluated to compare the two techniques. Statistical analysis showed that most CTV and rectum parameters were significantly larger for SA plans than for DA plans ( P  < 0.05). Furthermore, SA plans had fewer MUs and were less complex ( P  < 0.05). The significant differences observed had no clinical significance, indicating that both plans are comparable in terms of target and OAR dosimetry when ID is considered. The use of SA plans is recommended for prostate cancer VMAT because they can be delivered in shorter treatment times than DA plans, and therefore benefit the patients.